2021
DOI: 10.7759/cureus.13259
|View full text |Cite
|
Sign up to set email alerts
|

The Pattern of Dyslipidemia in Chronic Liver Disease Patients

Abstract: A substantial proportion of patients with chronic liver disease had hyperlipidemia which varied with the severity of disease on Child-Pugh classification. Routine monitoring of the lipid profile of such patients is necessary for timely identification and management of dyslipidemia to improve the outcome of such patients. It also suggests an important role of lipid profile in the risk stratification and treatment of chronic liver disease patients and warrants further studies in this regard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
2
1
0
Order By: Relevance
“…On the pathway level, multiple genesets pointed to a reduced level plasma lipoprotein particle assembly and remodelling which indicates changes in lipid distribution. This aligns with the known dyslipidaemia in chronic liver diseases, including decreasing serum values of LDL, HDL, total cholesterol, and triglycerides with increasing severity of disease, based on which previous studies suggested that routine monitoring of lipid profiles can improve the outcome for CLD patients [ 70 ]. Furthermore, a down-regulation of response to metal ions was found which could be related to metallothioneins which protect against oxidative stress and are able to chelate heavy metals [ 71 ].…”
Section: Resultssupporting
confidence: 68%
“…On the pathway level, multiple genesets pointed to a reduced level plasma lipoprotein particle assembly and remodelling which indicates changes in lipid distribution. This aligns with the known dyslipidaemia in chronic liver diseases, including decreasing serum values of LDL, HDL, total cholesterol, and triglycerides with increasing severity of disease, based on which previous studies suggested that routine monitoring of lipid profiles can improve the outcome for CLD patients [ 70 ]. Furthermore, a down-regulation of response to metal ions was found which could be related to metallothioneins which protect against oxidative stress and are able to chelate heavy metals [ 71 ].…”
Section: Resultssupporting
confidence: 68%
“…On the pathway level, multiple genesets pointed to a reduced level plasma lipoprotein particle assembly and remodelling which indicates changes in lipid distribution. This aligns with the known dyslipidaemia in chronic liver diseases, including decreasing serum values of LDL, HDL, total cholesterol, and triglycerides with increasing severity of disease, based on which previous studies suggested that routine monitoring of lipid profiles can improve the outcome for CLD patients [70] Furthermore, a down-regulation of response to metal ions was found which could be related to to metallothioneins which protect against oxidative stress and are able to chelate heavy metals [71].…”
Section: Time-concordant Events Reflecting Disease Progressionsupporting
confidence: 75%
“…Protein-protein interaction TF-target gene interaction Induced TF Not induced TF Only at the same time Ordered or at the same time suggested that routine monitoring of lipid profiles can improve the outcome for CLD patients [51].…”
Section: Time-concordant Events Reflecting Disease Progressionmentioning
confidence: 99%